Self-Efficacy Mechanism in Farm Tourism Microentrepreneurship - Ferreira, Bruno; Morais, Duarte B.; Jakes, Susan; Brothers, Gene; Brookins, Craig (Frontiers in Psychology, 2022)
Tourism microentrepreneurship is an important farm diversification strategy, also contributing to the competitiveness of the destination. However, psychological and structural constraints seem to hold back farmers when it comes to starting or expanding tourism operations. We argue that social capital derived from farmers' social networks affords sources of entrepreneurial self-efficacy, which boosts entrepreneurial intention. Analysis of survey data from 207 farmers in North Carolina revealed an adequate SEM model fit and strong significant relationships between bridging social capital and tourism microentrepreneurial self-efficacy. Internal self-efficacy factors were strongly and significantly associated with entrepreneurial intention. Triangulation with qualitative data from participatory action-research reinforced the importance of informal networking processes to model entrepreneurial behavior that boosts self-efficacy and reaffirms microentrepreneurial intentions. However, external self-efficacy was not significantly associated with farmers' entrepreneurial intentions, which may be attributable to ambiguous agritourism policy.